FACTORS AFFECTING PLOWING QUALITY INDICATORS - Sokolik, S. P.; Rudenko, V. A. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2021)
The article investigates the influence of such parameters of the machine unit on the quality indicators of plowing as: speed of movement, set plowing depth, surface type. The analysis of the field experiment data made it possible to determine the optimal pa-rameters of the tillage machine speed and tillage depth, which provide a greater angle of rotation of the soil layer, less ridge and depth of the field surface. As well as according to theoretical ideas for plowing, the increase in plowing depth decreased, and increasing the speed of movement increased the angle of rotation of the soil layer. The speed of the machine affects the crest and depth of the field surface. With increasing velocity on both types of surface, the values of these indicators, although not significant, decreased. When plowing on a clean surface, the quality of plow performance was also better than plowing stubble background: the ridge of the field decreased in the range of 11.0 - 9.4% against 14.3 - 10.8%; the depth of the field decreased in the range of 21.0 - 18.1% against 25.0 - 21.5%.